1980
DOI: 10.46429/jaupr.v64i2.10229
|View full text |Cite
|
Sign up to set email alerts
|

Título en español.

Abstract: Sarcotesta, sclerotesta, endosperm and embryo of fresh and old (0 and 3 years, respectively) seeds of the P.R. 6-65 and P.R. 8-65 papaya varieties were separately analyzed by paper chromatography to determine the presence of natural growth inhibitor that might be responsible for the reduction in germination of papaya seeds during storage. The results showed that in the innermost seed parts (embryo and endosperm) endogenous growth promoters were found while the outermost structures (sarcotesta and sclerotesta) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
3

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
4
0
3
Order By: Relevance
“…It was detected that maximum radicle length was observed for C. album, A. fatua and E. helioscopia. Similar, results were obtained in bioassays with lettuce seeds (Gherardi and Valio, 1976;Chow and Lin, 1991) and by Reyes et al (1980) with cucumber seeds. Chow and Lin (1991) used extracts of papaya, which showed that there is a higher concentration of inhibitors in the sarcotesta, canceling the germination of lettuce seeds, which had already been observed by Gherardi and Valio (1976).…”
Section: Allelopathic Potential Of C Papayasupporting
confidence: 80%
“…It was detected that maximum radicle length was observed for C. album, A. fatua and E. helioscopia. Similar, results were obtained in bioassays with lettuce seeds (Gherardi and Valio, 1976;Chow and Lin, 1991) and by Reyes et al (1980) with cucumber seeds. Chow and Lin (1991) used extracts of papaya, which showed that there is a higher concentration of inhibitors in the sarcotesta, canceling the germination of lettuce seeds, which had already been observed by Gherardi and Valio (1976).…”
Section: Allelopathic Potential Of C Papayasupporting
confidence: 80%
“…Lange (5) reported that germination was accelerated after removing the sarcotesta and that a water-soluble extract from seeds inhibited germination. Reyes et al (7) also found inhibitors in the sarcotesta and seed coat.…”
mentioning
confidence: 93%
“…A problem associated with seed propaga tion of papaya is poor germination (2,5,6). Several workers have isolated growth inhib itors from papaya seeds and have attributed sporadic germination to these substances (1,5,7). Lange (5) reported that germination was accelerated after removing the sarcotesta and that a water-soluble extract from seeds inhibited germination.…”
mentioning
confidence: 99%
“…The seeds of papaya are enclosed within a gelatinous sarcotesta (aril, or outer seed coat which is formed from the outer integument.) which can prevent germination (Reyes et al, 1980) [15] . Before sowing of seeds is soaking in water or water soluable endogenous hormones has been reported to promote the germination.…”
Section: Introductionmentioning
confidence: 99%